ESTIMASI DANA MASYAKARAT MELALUI VALUASI EKONOMI KERUSAKAN TERUMBU KARANG DI DESA POKA KOTA AMBON - Eygner Talakua (Jurnal Ilmu Lingkungan, 2019)
Ambon Bay, Ambon City is a region with high anthropogenic pressure and is very influential on coastal and marine resources, especially coral reefs. Damage to coral reefs in Ambon Bay occurred in Poka Village, handling has been done through the rehabilitation program with coral transplantation techniques, but the need for support and community participation in its management. One of the factors not yet successful management of coral reefs is lack of funds, whereas according to the rules of fund of coral reef management activities one of them can be sourced from the community. This study aims to determine the perception of the community on the existence of coral reefs, analyze the economic value of coral reef damage, and estimate community funds to repair damage to coral reefs in Poka Village, Ambon City. The study was conducted from January to May 2018 using case study method. A sample of 107 heads of households was obtained through proposive sampling and techniques of economical sampling of economies. The data analysis consisted of the analysis of community perception using the likeness scale on three indicators: knowledge, benefit, and coral reef damage; analysis of non-market economic valuation through CVM method; and estimates of community funds through the calculation of the total value of willingness to pay based on the number of people who are willing.The results showed that: 1). The perception of most of the people is very know and know the existence of coral reefs in Poka Village, only a small perception of hesitate and do not know; 2). There is a relationship of perception and willingness to pay the community to repair damage to coral reefs in Poka Village; 3). The economic value of coral reef damage is Rp. 4.288.000, - / month or Rp 51.456.000, - / year; and 4.) The estimation of community fund for coral reef damage in Poka Village is Rp 3,888,322,95 / month or Rp 46,659,875,46 / year.